THE ANTECEDENTS OF CHANGES IN PURCHASING PATTERNS DURING COVID-19 OUTBREAKS: AN INSIGHT FROM MALAYSIAN CONSUMERS - Arman Hj. Ahmad; Amy Emylia Natasya Muhammad Rakieein; Norsyahira Afiqah Abdel Hikim; Nur Azira Che Nawi; Sharipah Abdul Latip; Asbah M. Hum (Cita Konsultindo Research Center, 2022)
COVID-19 affected all parts of the world and infected millions of people. In 2020, more than half of the world’s population experienced a lockdown with strong containment measures which have changed lifestyles and human behaviour. This study aimed to explore the changes in consumers’ purchasing patterns from offline to online in Malaysia during the COVID-19 pandemic and propose a comprehensive framework to be scientifically tested in the future. The existing available literature was reviewed to discover the main reasons that would influence the changes in purchasing patterns from offline to online during the pandemic outbreak. Variables taken into the analyses are awareness of government law, social distancing, method of payment, and the relevance of price and quality. This paper proposed the sample of Malaysian consumers who should be randomly selected for the data collection considering the benefit of this technique whereby each individual in the large population has the same probability of being selected and with the assumption that all consumers with eligible purchasing power are affected by the outbreaks of the pandemic. This research predicted that the behaviour of Malaysian citizens particularly their purchasing patterns has changed due to the crisis COVID-19 pandemic with the existence of the above variables. The migration from offline to online purchasing patterns has reinforced the growing trend of online shopping. It has encouraged experimentation, coaxing consumers to explore different ways to access products and services. This paper opens doors for more opportunities for future research to discover a wider area in different regions, countries or ASEAN in the same setting to gain more consistent insights. Future researchers who are in the same interest might add other relevant external influence factors, such as the type of platform citizens use to buy online, and the influence of demographical elements on the purchasing behavioural changes. The deeper studies on consumer behaviours and feedback after sales, the target sample could be based on different ranges of age, educational backgrounds, and average income. As the different criteria, factors and different environments could generate different perspectives and research results which will enrich the literature and knowledge on consumerism.